2014
DOI: 10.1371/journal.pone.0084977
|View full text |Cite
|
Sign up to set email alerts
|

Subject-Specific Increases in Serum S-100B Distinguish Sports-Related Concussion from Sports-Related Exertion

Abstract: BackgroundThe on-field diagnosis of sports-related concussion (SRC) is complicated by the lack of an accurate and objective marker of brain injury.PurposeTo compare subject-specific changes in the astroglial protein, S100B, before and after SRC among collegiate and semi-professional contact sport athletes, and compare these changes to differences in S100B before and after non-contact exertion.Study DesignLongitudinal cohort study.MethodsFrom 2009–2011, we performed a prospective study of athletes from Munich, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 27 publications
4
41
1
Order By: Relevance
“…in several experimental or human studies. But some of these were not significantly elevated in patients with SCI compared with patients without any neurologic lesions (cleavedTau) (28) or the detection of MBP in the CSF is lower (29) or some are also found in other cells, such as adipocytes (S100β) (30). Also, there are few clinical studies for the majority of them or there are problems related to their accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…in several experimental or human studies. But some of these were not significantly elevated in patients with SCI compared with patients without any neurologic lesions (cleavedTau) (28) or the detection of MBP in the CSF is lower (29) or some are also found in other cells, such as adipocytes (S100β) (30). Also, there are few clinical studies for the majority of them or there are problems related to their accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…A number of other studies have shown an increase in serum S100β levels after concussion (Kiechle et al, 2014; Shahim et al, 2014) and even subconcussive head impacts. These reports have produced similar results, finding that mean S100β levels are 0.113 ± 0.052 ng/ml 1 h post-gameplay compared to pre-game means of 0.061 ± 0.019 ng/ml (Puvenna et al, 2014; Marchi et al, 2013).…”
Section: Serological Biomarkers For Brain Injurymentioning
confidence: 92%
“…However, poor association with other prognostic parameters raised questions regarding whether or not the increase in S100β was due to CNS-damage. Another recent study attempted to distinguish concussion-related elevations in serum S100β from the effects of exercise in contact sport athletes (Kiechle et al, 2014). First, pre-season baseline S100β levels were measured in 46 athletes.…”
Section: Serological Biomarkers For Brain Injurymentioning
confidence: 99%
“…Tau-C, but not Tau-A, was elevated after concussion; increased Tau-A at 144 hours was associated with persistent symptoms 69. S100b was increased 3 hours after concussion but not at days 2, 3, 7 or after exertion 71. Elevated glial fibrillar acidic protein was seen <24 hours postconcussion but not between 24 and 72 hours after injury; the change at <24 hours was associated with symptoms 72.…”
Section: Fluid (Blood and Urine) Biomarkersmentioning
confidence: 95%